«Color Revolutions» in Post-Soviet States as a Socio-Political Phenomenon: Defenition and Basic Views - D. A. Iglin (Проблемы постсоветского пространства)
This article deals with the problems of «color revolutions» and their occurrence in the former states of the USSR. The ambiguity of the results of these revolutions stipulate the importance and relevance of the topic research. Also it should be noted that the term «color revolutions» has two basic definitions: it is non-violent overthrow of the existing political power in the country, the second is used to refer to the methods and ways to implement a series of protests, wearing non-violent nature. Scientists from different countries continue discussions and debates on the subject, but no one doubts the fact that the «color revolution» is quite an urgent problem to date, and this issue requires a serious and thorough analysis. This article explores not only the basic views and approaches considering the phenomenon of «color revolutions». Also exemplified description and characterization of precedents of these revolutions in Georgia and Ukraine. From these examples, the authors made conclusion that the «color revolutions» in spite of its mass and momentum did not bring any changes in the political sphere of the country in which they originated. Hopes for the new political leaders and their governments, were not justified, as the political, economic and social problems, because of which the revolution occurred, remained unresolved.